Opportunities and Challenges of E- Payment System in India (International Journal of Scientific Research and Management (IJSRM), 2017)
Now a day’s world changed to digital world. India tries to stepping towards e-payment system. Electronic payment system is a payment system through an electronic network. In other words e-payment is a method in which a person can make Online Payments for his purchase of goods and services without physical transfer of cash and cheques, irrespective of location and time. Today India is at a stage of demonetization so; in the present scenario this study is inevitable to makes electronic payments at any time through the internet directly to manage the e-business environment. This study aimed to identify the issues and challenges of electronic payment systems and offer some solutions to improve the e-payment system. Epayment system not only provides more opportunities but many threats also.